Analysis of Chemical Characteristics of PM2.5 by Region in Chungnam - Hwang, Kyucheol; Park, Sechan; Gahye Lee, Sujin Noh; Kim, Jeongho; Lee, Jae Young; Park, Jong Sung; Kim, Jong Bum (Journal of Korean Society for Atmospheric Environment, 2023)
In a national effort to enhance air quality, 923 air quality monitoring stations (AQMS) have been set up nationwide. However, AQMS measure only six pollutants (SO2, NO2, PM10, PM2.5, CO, and O3). To understand regional PM2.5 traits, it’s effective to analyze its chemical composition. Our research centers on the Chungnam region, where four sites (Pado, Seonghwang, Songsan, and Sagok) conduct near real-time PM2.5 chemical measurements. Using 2021 data, we analyzed annual and seasonal averages for each site. Across these sites, emissions of organic carbon (OC), nitrate (NO3-), and sulfate (SO42-) were predominant. SO42- levels rose in summer, while NO3- increased in winter, displaying a typical trend. During the study period, three cases of high and low PM2.5 concentrations were selected for back-trajectories analysis. For high concentration cases, ion components exhibited higher proportions, whereas in low concentration cases, the proportion of OC increased, and NO3- proportions significantly decreased. To comprehend regional emission characteristics, national emission inventory data was analyzed. While NOx and CO emissions were dominant in most areas, Seonghwang region stood out with VOC emissions predominantly influenced by organic solvents. Chungnam, although currently classified as part of the central region, is actively pursuing air quality enhancement initiatives under a standardized policy framework. Nevertheless, based on the insights gleaned from this study, there is a compelling case for the introduction of region-specific policies to yield more effective outcomes. This underscores the need to tailor air quality improvement strategies according to the unique emission profiles and characteristics of individual regions.
Keywords: Air quality; Chemical composition; Chuncheongnam-do (Chungnam); Emission; PM2.5